Objectivity of historical knowledge and critical rationalism (The problem of the possibility of history as science revisited) - Panafidina, Oksana (Actual Problems of Mind, 2017)
The paper considers the conception of the scientific objectivity as developed within the framework of critical rationalism by Karl Popper. The autor proposes to apply its key principles to the theory of historical knowledge, and argues to the effect that it is possible to obtain objectivity in the science of history, but not as objectivity of an historian, but as characteristics of the historical knowledge.